2012
DOI: 10.1186/1749-8090-7-67
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of postoperative mediastinitis in cardiac surgery; negative pressure wound therapy versus conventional treatment

Abstract: BackgroundThe aim of the present study is to compare negative pressure wound therapy versus conventional treatment outcomes at postoperative mediastinitis after cardiac surgery.MethodsBetween January 2000 and December 2011, after 9972 sternotomies, postoperative mediastinitis was diagnosed in 90 patients. The treatment modalities divided the patients into two groups: group 1 patients (n = 47) were initially treated with the negative pressure wound therapy and group 2 patients (n = 43) were underwent convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 29 publications
5
35
1
5
Order By: Relevance
“…In the current study, significant purulent sternal wound complications -infection of the subcutaneous tissue of the sternum and mediastinal disorders -occurred in 35 patients (0.86%). The data published by other authors are similar, the rate of infection being from 0.5% up to 10% [1,2,4,[7][8][9][10]. The proportion of deaths that occurred in patients treated with VAC in this study (4.2%) does not differ from the data presented by other authors, but the spectrum of bacteria in the material is different [1,4,7].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In the current study, significant purulent sternal wound complications -infection of the subcutaneous tissue of the sternum and mediastinal disorders -occurred in 35 patients (0.86%). The data published by other authors are similar, the rate of infection being from 0.5% up to 10% [1,2,4,[7][8][9][10]. The proportion of deaths that occurred in patients treated with VAC in this study (4.2%) does not differ from the data presented by other authors, but the spectrum of bacteria in the material is different [1,4,7].…”
Section: Discussionsupporting
confidence: 64%
“…Strains of Gram-positive cocci represented only 20% of the infections, while in most authors' reports the percentage of infections exceeds 40%. In the present study, however, over 70% of infections were caused by Gram-negative rods, in contrast to other studies, where these bacteria were responsible for only 20-30% of the complications [1,2,4,10,11]. According to Gårdlund et al, mediastinum infections can be divided into 3 types.…”
Section: Discussioncontrasting
confidence: 49%
“…More recently, surgical revision with debridement, open dressing, and secondary closure, with or without pectoral muscle or omental flap transfer, are now used (Douville et al, 2004;. The interval to closure by this method remains unclear; variations in clinical practice include early closure within 48 hours or multiple debridements and packing until bacteriology samples are negative before closure with or without flap (Berdajs et al, 2011;Deniz et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The continual drainage of bacteria, debris, and exudates by negative wound pressure enhances microcirculation and accelerates tissue granulation Morykwas et al, 1997). Prompted by its increasing use, several studies have found the clinical effect of VAC to be comparable to traditional closed drainage or open packing, with improvement in sternal wound healing, reinfection rates, length of intensive care unit stay, and possibly mortality (Deniz et al, 2012;Risnes et al, 2012;Sjogren et al, 2005aSjogren et al, , 2005bVos et al, 2012). The effect of bacterial load with VAC, however, has had conflicting results (Assadian et al, 2010;Lalliss et al, 2010;Moues et al, 2004) with some studies showing bacterial accumulation, up to 10 4 -10 6 colonies of bacteria per gram of tissue (Weed et al, 2004;Yusuf et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…These infections are considered as severe complications; with high rates of morbidity and mortality, between 14 and 47%, representing high costs to the health system 6 , 8 - 9 .…”
Section: Introductionmentioning
confidence: 99%